Determinan Perilaku Konsumsi Tablet Tambah Darah Pada Remaja Putri Di Indonesia: Literature Review - Hervilanti, Putri; Flora, Rostika; Sunarsih, Elvi (Yayasan Jompa Research and Development, 2025)
ABSTRACT Adolescent girls are vulnerable to experiencing anemia due to low hemoglobin levels. The increase in cases globally demands appropriate prevention efforts, one of which is adherence to iron supplement tablet (TTD) consumption. This study aims to identify the factors influencing TTD consumption behavior among adolescent girls. The method used is a narrative review of 20 scientific articles published from 2019 to 2024 from the Google Scholar and PubMed databases, focusing on risk factors and behavioral determinants. The analysis results show that knowledge, attitudes, peer support, parental involvement, teachers, and health workers are the main factors influencing TTD consumption behavior. These findings can be used as a basis for formulating educational strategies and nutritional interventions to reduce the prevalence of anemia among adolescents. Keywords: Factors, Anemia, Iron Supplement Tablets and Adolescents